Analisis Peningkatan Kemampuan Kognitif Mahasiswa Setelah Penerapan Lms Resolva - Aditya Abdulloh Masykur; Rizky Basatha (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The learning process of Object-Oriented Programming (OOP) using Java for undergraduate students of Information Technology Education (PTI) tends to be conventional and teacher-centered. The absence of interactive media and the lack of Problem Based Learning (PBL) integration in the existing system cause students to struggle in understanding programming logic. This study aims to develop a website-based Learning Management System (LMS) named "Resolva" that integrates PBL syntax and an online compiler to improve students' cognitive abilities. The research method used is Research and Development (R&D) adapting the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects involved 30 undergraduate students of PTI Class of 2022 A, utilizing a One-Group Pretest-Posttest design. Data collection instruments included expert validation sheets, cognitive tests (pre-test and post-test), and the User Experience Questionnaire (UEQ). The results showed that the "Resolva" LMS is highly feasible for use, with validation scores of 91.76% for teaching modules, 89.34% for materials, 87.5% for test questions, and 74% for media, alongside a functionality test success rate of 97.92%. There was a significant improvement in cognitive abilities, evidenced by the Paired Sample t-Test (p < 0.001) and an average N-Gain of 0.6067 (moderate category). User response testing through UEQ indicated "Positive" criteria across all six dimensions (Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty). It is concluded that the "Resolva" LMS is valid, practical, and effective in improving cognitive skills in Java programming and provides an excellent user experience.